Rapid genetic modification of mouse embryonic stem cells by inducible cassette exchange recombination - Iacovino, Michelina (2014)
Embryonic stem cell (ESC) differentiation is a useful tool by which to develop large quantities of cells in vitro representing early stages of embryonic development. A conditional gene expression system allows interrogation of factors at specific time points in the differentiation of ES cells to defined cell types. We have developed a method for rapidly generating conditional inducible murine ES cells by targeting genes into an Inducible Cassette Exchange (ICE) locus. The ICE locus encodes a doxycycline-inducible floxed Cre, which replaces itself with an incoming floxed gene of interest. The derivative cell lines, selected in G418, thus bear doxycycline-inducible transgenes. We provide detailed methods for performing ICE recombination and generating derivative doxycycline-inducible cell lines.